Legal impact of robots in civil liability and taxation: What we know, trends and challenges - Cebola, Cátia Marques (2022)
Robotics is an unavoidable reality in today's global society. Nevertheless, issues relating to the civil liability and taxation of robots still represent an important field of scientific research. According to the International Robotics Federation, 420,870 units of industrial robots were sold in 2019 and in Europe the average density of robots in industry was 14% per 10,000 employees in 2018. This study aims to analyse the legal concerns of robotization (introduction of robots in organizations) at civil and tax liability level. To this end, will be made a compilation of legal prescriptions which may undergo changes due to the progressive robotization in Portugal. Based on this legal compilation, will be studied which legal changes have to be introduced or if they are necessary, in order to produce a positive balance between the inevitable changes operated by robotization (e.g. reduction of current jobs, tax revenues decrease or responsibility disclaimer for possible damage caused by robots) versus the insurmountable need for tax revenue so that the State can continue to provide quality public services and implement public policies that are fundamental to the country's sustainable development. Legal regulation is the path outlined in the European Commission's White Paper on Artificial Intelligence presented on 19/02/2020, which supports a regulatory approach with a dual objective of promoting robotization and address the risks associated with certain uses of this new technology. Analysing how legislation at civil and tax liability level should serve to compensate and rebalance the impact of robotization in Portugal is the basis of this paper.